Valor de la ecografía en el diagnóstico de los tumores de partes blandas en extremidades - Yamila Almaguer Fernández; Yolennys Miranda Pérez; Lisvette Ochoa Gómez; Mairelis Machado Verdecia; Karelia Ramírez Calvo (Correo Científico Médico)
RESUMEN